Cytomegalovirus Colitis Masquerading as Apple-Core Lesion after Systemic Chemotherapy in a Patient with Relapsed Acute Myeloid Leukemia. (20th March 2018) - An, Jong; Brownell, Jason; Barker, Darrell; Stockinger, Theresa; Brady, Robert; Cebe, Katherine; Baur, Russell
Abstract : We report the case of a 71-year-old male with relapsed acute myeloid leukemia who developed cytomegalovirus (CMV) colitis presenting as an apple-core lesion during induction chemotherapy. CMV infection occurs rarely during induction chemotherapy for acute myeloid leukemia. CMV infection is usually observed in patients with acquired immune deficiency syndrome (AIDS) and in those on immunosuppressive agents following bone marrow transplant. Although rare, CMV colitis should be considered in patients who are critically ill after systemic chemotherapy as it can cause significant morbidity and mortality.